my request is simple, explain the image i present to you
Follow Math Help Forum on Facebook and Google+
Originally Posted by steveebee my request is simple, explain the image i present to you From $\displaystyle (a+b)(a-b) = b(a-b) \Rightarrow a+b = b$ you divide by $\displaystyle (a-b)$, but $\displaystyle a=b \Rightarrow a-b = 0 $ thus you divided by zero. just to clarify: you can't divide by zero.
Defunkt, you found the loophole in that falacious argument neatly, wow!..... . steveebee, more here Classic Fallacies
View Tag Cloud